Innovation in Chemistry teaching: Optimized method for saponification index (Research, Society and Development, 2025)
The Saponification Index (SI) determines the amount (mg) of base required to saponify 1g of oil. It is related to the size of the fatty acids in the oil and is one of the ways to assess its quality and identity. For soybean oil, the SI should be between 189 and 195 mg KOH/g. Optimizing the method for determining the SI is crucial for chemistry education, both in technical courses and higher education, as it should utilize practical analytical methods to integrate practical and theoretical knowledge in order to enhance learning. This work aimed to optimize the method for determining the SI by adjusting variables such as reaction time, preparation of the KOH solution with diluted alcohol, comparing the execution of the blank sample subjected to the standard process and just through titration of the solution, and reducing equipment based on existing methods in the literature, for application in experimental classes of higher education courses. Regarding the use of the 4% KOH solution with diluted alcohol, the maximum possible dilution of alcohol was 80%. It was possible to reduce the time to 30 minutes at a temperature of 65 ± 2ºC in a water bath, without the need for condensers. As a result of the research conducted after the practical class, 66.6% of the students found the method viable and it provided an understanding of the topic. It can be concluded that the method for determining the SI can be optimized without compromising the reliability of the results, being effective, with results for soybean oil within legal standards, and received positive evaluations and feedback from the students.